Increasing Iron and Reducing Phosphorus Grades of Magnetic-Roasted High-Phosphorus Oolitic Iron Ore by Low-Intensity Magnetic Separation–Reverse Flotation - Xiao, Junhui; Zhou, Lingli (Processes, 2019)
High-phosphorus oolitic iron ore, treated by suspended flash magnetic roasting, contained 42.73% iron (mainly present as magnetite) and 0.93% phosphorus (present as collophane). Low-intensity magnetic separation (LIMS) was combined with reverse flotation to increase the iron and reduce the phosphorus contents of the roasted product. The results showed that an optimized iron ore concentrate with an iron grade of 67.54%, phosphorus content of 0.11%, and iron recovery of 78.99% were obtained under LIMS conditions that employed a grind of 95% −0.038 mm and a magnetic field of 0.10 T. Optimized rougher reverse-flotation conditions used a pulp pH of 9 and dosages of toluenesulfonamide, starch, and pine alcohol oil of 800 g/t, 1000 g/t, and 40 g/t, respectively; optimized scavenging conditions used a pulp pH of 9 and dosages of toluenesulfonamide, starch, and pine alcohol oil of 400 g/t, 500 g/t, and 20 g/t, respectively. Study of the mechanism of phosphorus reduction showed that the toluenesulfonamide could be adsorbed on the surface of quartz after the action of starch, but adsorption was significantly weakened. The starch inhibitor negatively affected adsorption on quartz, but positively influenced adsorption of phosphorus minerals.